Ensino de língua inglesa com crianças: saberes docentes e práticas pedagógicas em tempos pandêmicos - Santos, Jhonatan Carvalho (2022)
Discussions about Teaching English with Children are gaining more and more space within the areas of Applied Linguistics and Education, so much so that I have noticed a growing search for investigations that reveal how the process of teaching and learning English Language with Children is developed since there are no public educational policies in Brazil that support and contribute to the initial training of teachers who work in this teaching context. If, a priori, it was already possible to observe a huge teaching effort regarding pedagogical practice, given the current pandemic context (2020-2022), in which classes began to be taught in an emergency online remote teaching format, teachers needed to (re)build their teaching activities immediately, in order to meet this new educational conjuncture. Therefore, with this research, I aim to analyze the (re)construction of teaching knowledge in English language teaching practices with children in the age group that integrates the segments of Early Childhood Education and the Initial Years of Elementary School of regular private schools and schools of languages in Vila Velha/ES e Vitória/ES during the period of the Covid-19 pandemic between the years 2020 and 2021. In this way, was evidenced the context of action of the teachers invited to participate in the research that work in these contexts of teaching. To this end, I anchored this study in a qualitative-interpretative perspective of an exploratory nature, using as a method of investigation a standardized electronic questionnaire and semi-structured interviews, both online. As a result, I observed: (i) that teaching knowledge is supported by initial or continuing education, enabling participants to conceive reasons for the importance of learning an additional language from childhood, (ii) that this knowledge also comes from the pedagogical experience in private educational institutions where there has been a longer use of digital technologies and (iii) that the social and economic conditions of children are important aspects for carrying out remote educational activities in the midst of the pandemic. Finally, this research offers contributions for teachers to reflect on their training paths in order to (re)build their own teaching knowledge, aiming at a more critical, conscious and horizontal language education with children.